2012
DOI: 10.1353/hpu.2012.0066
|View full text |Cite
|
Sign up to set email alerts
|

Driving to Better Health: Cancer and Cardiovascular Risk Assessment among Taxi Cab Operators in Chicago

Abstract: While a number of investigations of the health of taxi cab drivers have been conducted in Europe, Asia, and Africa, virtually none have been conducted in the United States. We undertook a survey of taxi cab operators in the Chicago area to understand better their health status and health promotion practices. The survey was completed by a convenience sample of 751 Chicago taxi drivers. Taxi drivers had low rates of insurance coverage, fruit and vegetable consumption, and physical activity compared with the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 28 publications
(26 reference statements)
0
38
0
2
Order By: Relevance
“…A survey of Chicago drivers found only 5% met recommended levels of fruit and vegetable intake. 11 Sixty percent also reported that they were uninsured, 11 much higher than the national average of 17%. 43 In a study conducted in New York City (NYC) among South Asian taxi drivers, 40% of drivers had no usual source of healthcare.…”
Section: Introductionmentioning
confidence: 95%
“…A survey of Chicago drivers found only 5% met recommended levels of fruit and vegetable intake. 11 Sixty percent also reported that they were uninsured, 11 much higher than the national average of 17%. 43 In a study conducted in New York City (NYC) among South Asian taxi drivers, 40% of drivers had no usual source of healthcare.…”
Section: Introductionmentioning
confidence: 95%
“…1,11 Estos trastornos se derivan de la mala alimentación y el sedentarismo que se asocian, a su vez, a la escasa cantidad de tiempo libre y de descanso. 12 El exceso de peso es un factor de riesgo para desarrollar diabetes tipo 2 y problemas cardiovasculares. Ambos problemas se han observado entre los taxistas.…”
Section: Condiciones De Trabajo Y Salud En Conductores De Taxiunclassified
“…Todos estos problemas son prevalentes en la industria del taxi a nivel global. 11,12 Entre los conductores que participaron de este estudio el sedentarismo está muy extendido, aunque los conductores consideraban la falta de actividad física como algo preocupante. Esto contradicción aparente puede explicarse por la falta de tiempo disponible que resulta de la extensión de la jornada laboral.…”
Section: Globalunclassified
“…Taxi drivers are predominantly male and frequently lack insurance coverage [2]. Given the sedentary lifestyle of this occupation, taxi drivers are often at greater risk for cardiovascular disease (CVD), among other chronic illnesses, than the general population [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Taxi drivers are predominantly male and frequently lack insurance coverage [2]. Given the sedentary lifestyle of this occupation, taxi drivers are often at greater risk for cardiovascular disease (CVD), among other chronic illnesses, than the general population [2,3]. In addition to higher risk of underlying chronic health conditions and lack of medical insurance, taxi drivers and chauffeurs frequently come into close contact with a large number of individuals through this occupation, placing them at a potentially greater risk of acquiring and transmitting infectious diseases.…”
Section: Introductionmentioning
confidence: 99%